PENGUKURAN PRAKTIK GREEN ACCOUNTING DALAM MEWUJUDKAN KEBERLANJUTAN USAHA (STUDI PADA INDUSTRI PERHOTELAN DI KOTA DENPASAR) - Permana, Gusi Putu Lestara; Wullandari, Anak Agung Ayu Amira (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
The hotel industry in Bali Province faces risks related to dependence on tourism, which can harm the environment and local communities. This research aims to understand the implementation of green accounting practices in achieving business sustainability, especially in the hotel industry in Denpasar City, Bali Province. Apart from green accounting practices, to achieve business sustainability, it is also essential to consider the dimensions of organizational size as influencing regulatory factors or moderating variables. The population in this study consisted of Head of Accounting who worked in five-star hotels in Denpasar City, Bali Province. Sample selection used a saturated sampling technique, which was included in the Non-Probability Sampling category. The quantitative data is obtained through a questionnaire with a Likert scale as a measurement tool, which the respondents fill in. The collected data was then analyzed using simple linear and moderated regression analyses (MRA). The regression analysis results show that implementing green accounting practices has a positive and significant impact on business sustainability. However, simultaneously, organizational size does not significantly influence the relationship between green accounting practices and business sustainability.